2019
DOI: 10.1111/febs.15132
|View full text |Cite
|
Sign up to set email alerts
|

Direct regulation of Chk1 protein stability by E3 ubiquitin ligase HUWE1

Abstract: The HECT E3 ubiquitin ligase HUWE1 is required for a wide array of important functions in cell biology. Although HUWE1 is known to play a role in DNA damage signaling, the mechanism(s) that underlie this function remain elusive. HUWE1 regulates effectors of DNA replication and genotoxic stress tolerance. However, the loss of HUWE1 can also result in the accrual of significant endogenous DNA damage due to insufficient remediation of replication stress induced by an overabundance of key substrates. We discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…The DNA damage response (DDR) has been repeatedly shown to be controlled by K6-linked ubiquitination [ 21 25 ]. Pioneering studies reported K6-linked auto-ubiquitination of BRCA1-BARD1, a major DDR complex [ 21 ], and demonstrated the formation of K6-linked chains during replication stress and double-strand break repair [ 22 , 26 ].…”
Section: Lysine 6—autophagy and The Dna Damage Responsementioning
confidence: 99%
“…The DNA damage response (DDR) has been repeatedly shown to be controlled by K6-linked ubiquitination [ 21 25 ]. Pioneering studies reported K6-linked auto-ubiquitination of BRCA1-BARD1, a major DDR complex [ 21 ], and demonstrated the formation of K6-linked chains during replication stress and double-strand break repair [ 22 , 26 ].…”
Section: Lysine 6—autophagy and The Dna Damage Responsementioning
confidence: 99%
“…tumorigenesis (50)(51)(52)(53)(54). HUWE1 also plays important roles in regulating the DNA damage response (DDR) by targeting histones, MCL-1, and Chk1 (44,45,55,56). In addition, clinical evidence and exome sequencing revealed that HUWE1 mutations cause X chromosome-linked intellectual disability (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…The HECT family member HUWE1 (HECT, UBA and WWE domain containing protein 1, also known as Mule/ARF-BP1/LASU1/HECTH9) was initially shown to degrade three key regulators of stress and survival: Mcl1, p53, and Myc [6][7][8] . A growing list of HUWE1 substrates has since been reported 9 , including the stress-responsive regulator of mTORC1 signaling, DDIT4 10,11 , and many DNA damage response factors, such as the BRCA1 tumor suppressor, TopBP1, Cdc6 and CHEK1 [12][13][14][15] . Loss of HUWE1 sensitizes cells not only to DNA damage, but also to a variety of other stressors, including both oxidative and hypoxic stress 9,[16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%